Integrative Temporo-Spatial, Mineralogic, Spectroscopic, and Proteomic Analysis of Postnatal Enamel Development in Teeth with Limited Growth - Pandya, Mirali; Liu, Hui; Dangaria, Smit J.; Zhu, Weiying; Li, Leo L.; Pan, Shuang; Abufarwa, Moufida; Davis, Roderick G.; Guggenheim, Stephen; Keiderling, Timothy; Luan, Xianghong; Diekwisch, Thomas G. H. (Frontiers in Physiology, 2017)
Tooth amelogenesis is a complex process beginning with enamel organ cell differentiation and enamel matrix secretion, transitioning through changes in ameloblast polarity, cytoskeletal and matrix organization, and affecting crucial biomineralization events such as mineral nucleation, enamel crystal growth, and enamel prism organization. Here we have harvested the enamel organ including the pliable enamel matrix of postnatal first mandibular mouse molars during the first eight days of tooth enamel development to conduct a step-wise cross-sectional analysis of the changes in the mineral and protein phase. Mineral phase diffraction pattern analysis using single-crystal, powder sample X-ray diffraction analysis indicated conversion of calcium phosphate precursors to fluorapatite from postnatal day 4 (4 dpn) onwards. Attenuated total reflectance spectra (ATR) revealed a substantial elevation in phosphate and carbonate incorporation as well as structural reconfiguration between postnatal days 6 and 8. Nanoscale liquid chromatography coupled with tandem mass spectrometry (nanoLC-MS/MS) demonstrated highest protein counts for ECM/cell surface proteins, stress/heat shock proteins, and alkaline phosphatase on postnatal day 2, high counts for ameloblast cytoskeletal proteins such as tubulin β5, tropomyosin, β-actin, and vimentin on postnatal day 4, and elevated levels of cofilin-1, calmodulin, and peptidyl-prolyl cis-trans isomerase on day 6. Western blot analysis of hydrophobic enamel proteins illustrated continuously increasing amelogenin levels from 1dpn until 8dpn, while enamelin peaked on days 1 and 2dpn, and ameloblastin on days 1-5dpn. In summary, these data document the substantial changes in the enamel matrix protein and mineral phase that take place during postnatal mouse molar amelogenesis from a systems biological perspective, including (i) high levels of matrix protein secretion and non-amelogenin enamel protein expression during the early secretory stage on postnatal day 2, (ii) conversion of calcium phosphates to apatite, peak protein folding and stress protein counts, and increased cytoskeletal protein levels such as actin and tubulin on day 4, as well as (iii) secondary structure changes, isomerase activity, highest amelogenin levels, and peak phosphate/carbonate incorporation between postnatal days 6 and 8. Together, this study provides a baseline for a comprehensive understanding of the mineralogic and proteomic events that contribute to the complexity of mammalian tooth enamel development.